Hybrid wildebeest (Artiodactyla: Bovidae) provide further evidence for shared signatures of admixture in mammalian crania - Rebecca Ackermann; James Brink; Savvas Vrahimis; Bonita de Klerk (South African Journal of Science)
The genus Connochaetes, Lichtenstein, 1814, contains two extant species, the blue wildebeest (C. taurinus, Burchell, 1823) and the black wildebeest (C. gnou, Zimmermann, 1780). In recent years, forced sympatry in confined areas within South Africa has led to interbreeding between these taxa and to fertile hybrid offspring. Here we report on a series of cranial characteristics of a hybrid wildebeest population culled at Spioenkop Dam Nature Reserve, KwaZulu-Natal, South Africa. Dental, sutural and horn morphological anomalies occur at high frequency within these animals. Similar cranial morphological anomalies have been shown in other mammalian hybrids and this study provides further evidence that such anomalies may characterise hybridisation more broadly across phylogenetically divergent mammalian groups, although the anomalies appear to differ in their expression across taxa. An increased ability to identify hybrids may also have important applications in the conservation of the endemic black wildebeest.